2011
DOI: 10.1007/s11259-011-9461-2
|View full text |Cite
|
Sign up to set email alerts
|

Viral distribution and lesions in Kunming mice experimentally infected with porcine circovirus type 2b

Abstract: The viral distribution and lesions in Kunming mice experimentally infected with porcine circovirus type 2b (PCV-2b) were investigated. Seventy special pathogen free mice were divided into 2 groups with 35 mice in each group. The test group (TG) was infected with PCV-2b, the control group (CG) was inoculated with sterile cell cultures. Five mice in each group were sacrificed at 3, 7, 14, 21, 28, 35 and 42 dpi (day post infection), respectively. Necropsies were performed on all mice and tissues were collected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…Sequence analysis showed that the PCV2 sequences from rodents were similar to those from pigs at the two farms, belonging to the PCV2b genogroup with low levels of nucleotide differences (Lorincz et al, 2010). Low level PCV2b replication could also be demonstrated in inoculated mice (Cságola et al, 2008; Deng et al, 2011). A report of PCV2 infection in cows found PCV2 DNA in 6/100 lung tissue samples from cows with respiratory disease and in 4/30 aborted bovine fetuses (Nayar et al, 1999).…”
Section: Phylogenetic Evidence For Cross-species Transmission Of Circmentioning
confidence: 96%
“…Sequence analysis showed that the PCV2 sequences from rodents were similar to those from pigs at the two farms, belonging to the PCV2b genogroup with low levels of nucleotide differences (Lorincz et al, 2010). Low level PCV2b replication could also be demonstrated in inoculated mice (Cságola et al, 2008; Deng et al, 2011). A report of PCV2 infection in cows found PCV2 DNA in 6/100 lung tissue samples from cows with respiratory disease and in 4/30 aborted bovine fetuses (Nayar et al, 1999).…”
Section: Phylogenetic Evidence For Cross-species Transmission Of Circmentioning
confidence: 96%
“…BALB/c mice were used as an animal model as previously described [6,7,18,19]. A total of 175 specific pathogen-free (SPF) female BALB/c mice 6 to 8 weeks old were obtained from the Experimental Animal Center of Henan Province (China).…”
Section: Methodsmentioning
confidence: 99%
“…Using the PCV2b-specific primers (5' -GGAGCTTCCAATCTCCC-3' , 5'-TAGGAGCTCCACACTCC-3'), the PCV2b DNA in mice was detected by PCR following the methods described in a previous study (9).…”
mentioning
confidence: 99%
“…The primary mouse anti-PCV2b sera preparation was as described in our previous study (9), and then sections were incubated with a 1:400 dilution of primary mouse antiPCV2b sera at 37 °C for 2 h. Following this, a 1:50 dilution of secondary anti-mouse IgG antibody with fluorescein (Zhongshan Golden Bridge Co. Ltd., Beijing, China) was added at 37 °C for 1 h; finally, it was photographed under a fluorescence microscope (Olympus, Tokyo, Japan).…”
mentioning
confidence: 99%